2011
DOI: 10.1074/jbc.m111.247601
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of tesA Reduces Cell Wall Lipid Production and Increases Drug Susceptibility in Mycobacteria

Abstract: Phthiocerol dimycocerosates (PDIMs) and phenolic glycolipids (PGLs) are structurally related lipids noncovalently bound to the outer cell wall layer of Mycobacterium tuberculosis, Mycobacterium leprae, and several opportunistic mycobacterial human pathogens. PDIMs and PGLs are important effectors of virulence. Elucidation of the biosynthesis of these complex lipids will not only expand our understanding of mycobacterial cell wall biosynthesis, but it may also illuminate potential routes to novel therapeutics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 49 publications
4
63
0
Order By: Relevance
“…[ 14 C]Propionate was added to each well at 0.2 mCi ml 21 (7.4 MBq ml 21 ) and the plates were incubated at 30 uC with rotary agitation (170 r.p.m.) for 24 h. After incubation, the OD 595 of the cultures was measured in a DTX Plate Reader (Beckman Coulter), and the cells were harvested for apolar lipid fraction extraction with a biphasic mixture of methanolic saline and petroleum ether, as reported previously (Chavadi et al, 2011b;Ferreras et al, 2008). The lipid extracts were subjected to radio-TLC for analysis of 14 C-labelled PGLs (using CHCl 3 /CH 3 OH, 95 : 5) and PDIMs (using petroleum ether/diethyl ether, 9 : 1) as described previously (Ferreras et al, 2008).…”
Section: Dpapa5cmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 14 C]Propionate was added to each well at 0.2 mCi ml 21 (7.4 MBq ml 21 ) and the plates were incubated at 30 uC with rotary agitation (170 r.p.m.) for 24 h. After incubation, the OD 595 of the cultures was measured in a DTX Plate Reader (Beckman Coulter), and the cells were harvested for apolar lipid fraction extraction with a biphasic mixture of methanolic saline and petroleum ether, as reported previously (Chavadi et al, 2011b;Ferreras et al, 2008). The lipid extracts were subjected to radio-TLC for analysis of 14 C-labelled PGLs (using CHCl 3 /CH 3 OH, 95 : 5) and PDIMs (using petroleum ether/diethyl ether, 9 : 1) as described previously (Ferreras et al, 2008).…”
Section: Dpapa5cmentioning
confidence: 99%
“…Thus, dissecting the molecular logic of PGL and PDIM biosynthesis not only will expand our general understanding of cell wall biosynthesis in mycobacteria of clinical significance, but also may reveal potential avenues for exploring the development of alternative therapeutics against selected mycobacterial infections (Ferreras et al, 2008;Quadri, 2007). These views have directed our previous studies of the biosynthesis of PGLs and PDIMs Chavadi et al, 2011b;Ferreras et al, 2008;He et al, 2009;Onwueme et al, 2004Onwueme et al, , 2005a, which include the development of the first PGL biosynthesis inhibitor (Ferreras et al, 2008). This inhibitor drastically reduces PGL production in several Mycobacterium species (Ferreras et al, 2008) using a mechanistic principle analogous to that of the first reported inhibitor of mycobacterial siderophore (iron chelator) production (Ferreras et al, 2005;Quadri, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations